2013
DOI: 10.1016/j.cell.2013.03.026
|View full text |Cite
|
Sign up to set email alerts
|

A Direct In Vivo RNAi Screen Identifies MKK4 as a Key Regulator of Liver Regeneration

Abstract: The liver harbors a distinct capacity for endogenous regeneration; however, liver regeneration is often impaired in disease and therefore insufficient to compensate for the loss of hepatocytes and organ function. Here we describe a functional genetic approach for the identification of gene targets that can be exploited to increase the regenerative capacity of hepatocytes. Pools of small hairpin RNAs (shRNAs) were directly and stably delivered into mouse livers to screen for genes modulating liver regeneration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
120
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 45 publications
0
120
0
Order By: Relevance
“…Indeed, in vivo RNA interference (RNAi) screens have identified MKK4 as a key regulator of liver regeneration (389), whereas studies in MKK7 Ϫ/Ϫ mice have revealed the critical need for MKK7 in axon elongation in the developing cerebral cortex (390). The compound disruption of both the MKK4 and MKK7 genes results in severe growth retardation and embryonic lethality (E9.5).…”
Section: Jnk Involvement In Embryonic Developmentmentioning
confidence: 99%
“…Indeed, in vivo RNA interference (RNAi) screens have identified MKK4 as a key regulator of liver regeneration (389), whereas studies in MKK7 Ϫ/Ϫ mice have revealed the critical need for MKK7 in axon elongation in the developing cerebral cortex (390). The compound disruption of both the MKK4 and MKK7 genes results in severe growth retardation and embryonic lethality (E9.5).…”
Section: Jnk Involvement In Embryonic Developmentmentioning
confidence: 99%
“…Plasmid-based expression of short hairpin RNA has been used to study the role(s) of HGF/c-Met and EGFR during liver regeneration in rats 15,16 , and stable delivery of pools of short hairpin RNAs into mouse livers lead to the identification of the kinase MKK4 as a major regulator of liver regeneration 17 . Additional siRNA delivery systems were invented to improve tissue specificity and low-dose efficacy.…”
mentioning
confidence: 99%
“…RNAi-based high-throughput screening has become a widely used method for identification of new components of diverse biological processes, including signal transduction, cancer, and host cell responses to infection (1,2). Genome-scale RNAi screens have led to identification of tumor suppressors (3), oncogenes (4), therapeutic targets (5), and regulators of ES cell (ESC) maintenance (6)(7)(8)(9)(10), tissue regeneration (11), viral infection (12), and antiviral response (13).…”
mentioning
confidence: 99%